Nature and Identity in Cross-Cultural Perspective
XVIII, 360 p.
Keywords: Nature and Identity in Cross-Cultural Perspective presents 20 essays which explore diverse cultural interpretations of the earth's surface. Contrasted with each other and with the potentially cosmopolitan culture of science, these detailed studies of ways in which different cultures conceptualise nature appear in the context of global environmental change. Understanding across cultural lines has never been more important. This book shows how individual cultures see their own histories as offering protection for nature, while often viewing others as lacking such ethical restraints. Through such writing a discourse of understanding and common action becomes possible. The authors come from the places they discuss, and offer passionate as well as scholarly visions of nature within their cultural homes. Audience: This volume is of interest to academics and professionals working in the fields of cultural geography, environmental history, environmental studies, history of environmental ideas, environmental education, landscape and literature, nature and culture. It can be used for courses in the above-mentioned areas and seminars in comparative literature. It can also be used as a complimentary text to provide cultural context to literary readings, and for seminars on cultural aspects of the environment.